(untitled) (International Journal of Innovative Technologies in Economy, 2018)
All world practice, experience of the developed countries, confirm convincingly, about a major role and place of industry in the structure of economy. With steady development of industry of связанны : macroeconomic and social stability, economic, power, food, technological and innovative security of country, level and quality of life of population. The modern state of national economy requires providing of the strong balanced growth of all industries of the industrial production sent to more complete satisfaction of necessities of population of country in modern, competitive products. In the article the attained results of Uzbekistan are considered an author and analysed in development of industry, and also problems are certain and ways are offered for further to stimulation and purposeful steady development of industry.